On the estimation of the remainder term in the multidimensional central limit theorem - Jasiūnas, H. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Г. Ясюнас. Об оценке остаточного члена в многомерной центральной предельной теореме H. Jasiūnas. Liekamoje nario įvertinimas daugiamatėje centrinėje ribinėje teoremoje